1988
DOI: 10.1021/ja00218a005
|View full text |Cite
|
Sign up to set email alerts
|

Proton NMR characterization of the catalytically relevant proximal and distal hydrogen-bonding networks in ligated resting state horseradish peroxidase

Abstract: Proton NMR spectroscopy of the low-spin cyanide complex of horseradish peroxidase, HRPCN, in H20 solution was used to examine exchangeable resonances of functionally important amino acids in the heme pocket and their role in hydrogen-bonding networks, which have been proposed to facilitate peroxidase catalysis. Spectra were analyzed by use of nuclear Overhauser effect and saturation-transfer spectroscopies, along with consideration of paramagnetic shift and relaxation.Definitive assignments could be made in sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
125
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(149 citation statements)
references
References 7 publications
15
125
0
Order By: Relevance
“…The resolved upfield spectral region displays several single-proton resonances and a few multiproton signals. Previous work on both heme model compounds and a number of heme peroxidases have firmly concluded that this spectral region encompasses the resonances from ␤-protons of the heme vinyl and propionate groups as well as those from some of the amino acid residues near the heme center (53,72,(77)(78)(79). The chemical shifts and the corresponding diamagnetic shift values predicted from Curie plot as well as the spin-lattice relaxation times for the hyperfine shifted resonances and their assignments in CPOCN are compiled in Table I, along with the corresponding parameters in MnPCN (72,80) and HRPCN (51) reported previously.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The resolved upfield spectral region displays several single-proton resonances and a few multiproton signals. Previous work on both heme model compounds and a number of heme peroxidases have firmly concluded that this spectral region encompasses the resonances from ␤-protons of the heme vinyl and propionate groups as well as those from some of the amino acid residues near the heme center (53,72,(77)(78)(79). The chemical shifts and the corresponding diamagnetic shift values predicted from Curie plot as well as the spin-lattice relaxation times for the hyperfine shifted resonances and their assignments in CPOCN are compiled in Table I, along with the corresponding parameters in MnPCN (72,80) and HRPCN (51) reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…This is anticipated, since the distal acid-base catalyst in CPO is a glutamic acid (6) rather than a histidine as in other heme peroxidases (24, 74 -76). The proton/deuteron exchange on the N⑀ atom of the distal histidine has been shown to be responsible for the observed solvent effect on heme resonances in several heme peroxidases (36,53,72).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yeast cytochrome c peroxidase, CcP, yielded the first crystal structure (37), while horseradish peroxidase, HRP, because of its much greater stability, yielded the more detailed NMR assignment and solution NMR characterization (1,15,38,39). The cyanide-inhibited complex mimics the catalytically active compound-II of heme peroxidases (40).…”
Section: Heme Peroxidasesmentioning
confidence: 99%